Clinical Effects of Mindfulness-Based Intervention in Patients With First Episode Psychosis and in Individuals With Ultra-High Risk for Transition to Psychosis: A Review - Vignaud, Philippe; Reilly, Karen T.; Donde, Clément; Haesebaert, Frédéric; Brunelin, Jérôme (Frontiers in Psychiatry, 2019)
Objectives. Recent clinical studies and meta-analyses have reported the clinical effects of mindfulness-based interventions as a complementary treatment for patients with schizophrenia, but their possible efficacy in patients with first episode of psychosis (FEP) and in individuals with ultra-high risk (UHR) of transition to psychosis is less clear. Here, we investigated the current evidence on the usefulness of mindfulness-based interventions in these two populations. Methods. We conducted a systematic search of the literature according to the PRISMA guidelines. Results. Among the 102 references retrieved, 9 responded to the inclusion criteria (8 in FEP patients and one in UHR individuals). In FEP patients, mindfulness interventions are well-tolerated and have a satisfactory level of adherence. The clinical benefits consist primarily of reduced anxiety and sadness and improved quality of life. None of the studies reported any increase in positive symptoms. Conclusion. Future sham-controlled studies with large sample sizes are needed to definitively conclude on the clinical interest of mindfulness-based interventions in FEP patients and UHR individuals as well as to understand their underlying mechanisms of action.